Advancing renewable energy in resource-rich economies of the MENA - Poudineh, R; Sen, A; Fattouh, B (Oxford Institute for Energy Studies, 2016)
As much of the world pushes ahead with the deployment of renewable energy, resource-rich MENA economies are lagging behind. For the region to catch up, new policies are required to remove barriers of entry to the industry and create investment incentives. This paper contends that while the main obstacles to deployment of renewables are grid infrastructure inadequacy, insufficient institutional capacity, and risks and uncertainties, the investment incentives lie on a policy instrument spectrum with two polar solutions: (i) the incentive is provided entirely through the market (removing all forms of fossil fuel subsidies and internalising the cost of externalities); or (ii) the incentive is provided through a full government subsidy programme (in addition to the existing fossil fuel subsidies). However, there is a trade-off between the two dimensions of the fiscal burden and political acceptance across the policy instrument spectrum, which implies that the two polar solutions themselves are not easily and fully implementable in these countries. Therefore, we propose a combinatorial approach in which the incentive for renewables deployment is provided through a partial renewable subsidy program and partial fossil fuel price reform in a way that balances the fiscal pressure on the government against political acceptability. Additionally, the paper argues that the fact resource-rich countries are behind advanced economies in electricity sector reform gives them a last-mover advantage in the sense that they can tap into years of international experience to avoid design mistakes and create a sustainable solution that is compatible with renewables deployment and their own context.